Equity through Guided Pathways in California Community Colleges: examining discursive (im)possibilities - Galan, Carlos A.; Felix, Eric R.; Salazar, Rogelio; Vásquez, Stephanie; Ortiz, Nathen; Franco, Citlalli (Frontiers in Education, 2025)
The California Community Colleges (CCC) system introduced the Guided Pathways (GP) framework as a large-scale system-wide transformation effort to improve completion rates and close equity gaps. This study analyzes how CCC campuses implemented the GP framework to address issues of racial equity through their 2021–2022 Scale of Adoption Assessment (SOAA) reports. Using Critical Race Discourse Analysis (CRDA), we examine how institutional language either names racial inequities and racism directly or, through silence and neutrality, reproduces them. In our findings we highlight that although many reports include equity language, they often avoid directly addressing race, racism, or the specific needs of students of color. Instead, in many instances reports favor vague, universal terms. In contrast, some colleges take race-conscious approaches, explicitly identifying racialized barriers and integrating equity-minded practices into curricular and structural redesign. These discursive choices demonstrate that GP does not guarantee equity; its effectiveness depends on how institutions define, communicate, and implement equity in their local contexts. By treating discourse as a space for ideological struggle, this study reveals the uneven nature of equity work in community colleges and emphasizes the need for sustained, race-explicit language and strategies to ensure GP drives institutional transformation rather than perpetuates racial inequities.